2019
DOI: 10.1088/1361-6560/aaf496
|View full text |Cite|
|
Sign up to set email alerts
|

Comparing Unet training with three different datasets to correct CBCT images for prostate radiotherapy dose calculations

Abstract: The colorbar range in figures 9(c), (e) and (g) in our article was unfortunately incorrect. The correct range is −15% to 15%, and not −2% to 2%. This error does not impact the quantitative analyses reported in the main body of the article or in other figures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
105
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 72 publications
(108 citation statements)
references
References 35 publications
2
105
1
Order By: Relevance
“…Studies using DL for pCT generation from CBCT are scarce for brain, 55 H&N, [13][14][15] pancreas, 38 or prostate cancer. [35][36][37]55,56 The studies involved an imaging analysis (pCT vs. reference CT), but only half of them evaluated the dose accuracy. Among the three H&N studies using DL for pCT generation from CBCT, [13][14][15] one involved training a U-Net neural network on 50 coregistered CBCT/CT images and performing a test based on data from 10 patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies using DL for pCT generation from CBCT are scarce for brain, 55 H&N, [13][14][15] pancreas, 38 or prostate cancer. [35][36][37]55,56 The studies involved an imaging analysis (pCT vs. reference CT), but only half of them evaluated the dose accuracy. Among the three H&N studies using DL for pCT generation from CBCT, [13][14][15] one involved training a U-Net neural network on 50 coregistered CBCT/CT images and performing a test based on data from 10 patients.…”
Section: Discussionmentioning
confidence: 99%
“…32 Some studies have recently proposed DLMs for pCT generation from CBCT, mainly for scatter correction. 33,34 Other studies proposed the DLM for pCT generation from CBCT in prostate, [35][36][37] pancreas, 38 and H&N, [13][14][15] for dose calculation. H&N studies have been performed using either U-Net or cycleGAN architectures to generate pCT from CBCT.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, Landry et al . evaluated the performance of a Unet on projection domain and image domain CBCT data and found that CBCT corrections in the image domain achieved lower mean error (ME) and MAE …”
Section: Introductionmentioning
confidence: 99%
“…23 Finally, Landry et al evaluated the performance of a Unet on projection domain and image domain CBCT data and found that CBCT corrections in the image domain achieved lower mean error (ME) and MAE. 24 In this work, we propose a deep learning method, a cycleconsistent adversarial network (cycle-GAN), based on paired CT and CBCT images to correct CBCT images. 25 The cycle-GAN framework is appealing for CBCT correction because it can efficiently convert images between the source domain and the target domain when the underlying structures are similar, even if the mapping between domains is nonlinear.…”
Section: Introductionmentioning
confidence: 99%
“…The use of in-room CT currently guarantees the most accurate definition of proton stopping power, and with a low-dose protocol, it is possible to limit the imaging dose to the patient to below 1 mGy per CT [23,24], similar to that delivered with CBCT [25]. CBCT for adaption is currently under investigation but extracting density information with the same accuracy as with CT [26][27][28][29][30] remains challenging. The use of MRI for daily imaging clearly has advantages of no imaging dose, but is currently only under investigation [31,32].…”
Section: Patientmentioning
confidence: 99%